Islamic Religious Education Teachers' Control over the Viral Trend of Imitating Impolite Language from TikTok Social Media in Shaping Students' Moral Character - Taukhid Mubarok; Siti Fatimah; Ahmad Mustofa Aqil; Rizka Ayu Amalia; Fardan Ali (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to analyze the influence of TikTok viral trends on students’ imitation of impolite language, examine the control strategies implemented by Islamic Religious Education (IRE) teachers, and identify the supporting and inhibiting factors affecting students’ moral character development through language regulation. This research employed a qualitative approach using a case study design at SD Negeri Jatibarang Lor 01. Data were collected through classroom observations, in-depth interviews, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. Data trustworthiness was ensured through source triangulation, technique triangulation, and member checking. The findings reveal that TikTok’s algorithm accelerates students’ imitation of impolite language by repeatedly exposing them to viral expressions and communication patterns that gradually become part of their daily interactions at school. IRE teachers address this phenomenon through intensive supervision, educative corrective feedback, habituation of polite language, integration of Islamic communication ethics into classroom instruction, exemplary behavior, reinforcement of a religious school culture, and continuous collaboration with parents. The study also identifies excessive smartphone use, limited parental supervision, peer influence, and the rapid expansion of digital culture as the primary obstacles to effective moral education. The novelty of this study lies in the development of an Integrative Educational Control Model, which combines Islamic moral education, digital literacy, teacher role modeling, character habituation, and family school collaboration as a comprehensive framework for mitigating the negative influence of TikTok on students’ moral character in the digital era.